PENGEMBANGAN BAHAN AJAR DAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA - pusfarini pusfarini; Sucipto Sucipto (Hipotenusa Journal of Research Mathematics Education (HJRME), 2019)
The development of teaching materials and learning media used by teachers in providing lessons is expected to help students master basic competencies. The method used in this research is a quantitative descriptive method, data collection is used essay tests. 23 Bandar Lampung. The population is 239 students spread over 6 classes. In the study, two classes were sampled, namely class VII D and VII E, totaling 80 students. Sampling using cluster random sampling technique. Data analysis using the t test formula. From the results of hypothesis testing using the statistical formula t-test, it was obtained thit = 4.71, in the similarity test the two averages for  = 0,05 were obtained   = 2.00, and For = 0.01 obtained   = 2.66. Because thit > tdaf f then the hypothesis Ho is rejected, meaning Ha is accepted. So it can be concluded that "there is an effect of applying the development of teaching materials and learning media in teaching mathematics to mathematics learning outcomes in class VII students in even semesters of SMP Negeri 23 Bandar Lampung. and For = 0.01 obtained =  = 2.39. Because thit > tdaf Ho is rejected, it means that Ha is accepted at the level of significance of   = 0.05 or 0.01, the value of thit is greater. Thus it was concluded that: "The average mathematics learning outcomes of students with the development of teaching materials and learning media are higher than the average mathematics learning outcomes of students without the development of teaching materials and learning media"